2009
DOI: 10.1016/j.jjcc.2009.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between exercise tolerance and muscle strength following cardiac rehabilitation: Comparison of patients after cardiac surgery and patients with myocardial infarction

Abstract: These data suggest that exercise intolerance in patients after heart valve surgery may in part depend on decreased muscular strength. Further studies are needed to assess whether the strategy of increasing muscular strength of lower limb by programmed resistance training could be effective for improving exercise intolerance in patients after heart valve surgery and symptomatic patients with heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 29 publications
3
18
0
Order By: Relevance
“…In addition, we found no significant difference in knee extension strength or resistance after 3 months of HB or CB training. This is consistent with previous studies [35,36]. Conraads et al, collected muscle strength data in 75 CAD patients before and after 12 weeks of an AIT or ACT CR program finding that muscle strength did not improve.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, we found no significant difference in knee extension strength or resistance after 3 months of HB or CB training. This is consistent with previous studies [35,36]. Conraads et al, collected muscle strength data in 75 CAD patients before and after 12 weeks of an AIT or ACT CR program finding that muscle strength did not improve.…”
Section: Discussionsupporting
confidence: 91%
“…Increased muscle strength and cardiac fitness reflect regular physical activity 1, 2, 3. This reflection is strongly associated with time-dependent exercise 4, 5.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have demonstrated that cardiac rehabilitation improves exercise tolerance and muscle strength in patients with myocardial infarction and in patients after cardiac surgery. In addition, Sumide et al [6] reported that the improvement in exercise tolerance was significantly correlated with the changes in lower limb leg strength in post-cardiac valve surgery patients (r = 0.51, P < 0.01). A positive and significant correlation between the change in peak VO 2 and the change in peak torque of knee extension (r = 0.50, P < 0.005) was also observed in the acute phase after a myocardial infarction (MI) in patients with a lower limb muscle volume of less than 22 kg at baseline [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, muscle testing was performed to test potential zero-order correlations between muscle diameter, muscle volume and muscle force and to investigate whether correlations found with CT are similar to those with US. Peripheral skeletal muscle strength of the lower limb may be assessed by isokinetic dynamometry and provides a reliable and safe assessment of dynamic muscle function [5,6]. …”
Section: Introductionmentioning
confidence: 99%